Emergency care for older people living with frailty: patient and carer perspectives. Issue 10 (6th September 2022) - Regen, Emma; Phelps, Kay; van Oppen, James David; Riley, Peter; Lalseta, Jagruti; Martin, Graham; Mason, Suzanne M; Conroy, Simon
Abstract : Background: Little is known about how frailty impacts on older people's experiences of emergency care, despite patient experience being essential to providing person-centred care. This qualitative study reports on the experiences of older people with frailty in the ED and their and their carers' preferences for emergency care. Methods: Older people (aged 75+ years) who were at least mildly frail and/or their carers, with current or recent experience of emergency care, were recruited from three EDs in England between January and June 2019. Data were collected via semi-structured in-depth interviews which explored participants' views on their recent experience of emergency care and their priorities and preferred outcomes. Interviews were audio-recorded, transcribed verbatim and analysed following the principles of the Framework approach. Results: Forty participants were interviewed: 24 patients and 16 carers who, between them, described ED attendances for 28 patients across the three sites. Often informed by previous negative experiences, there was a strong desire to avoid conveyance to EDs, and a sense of helplessness or acquiescence to attend. Although staff attitudes were on the whole seen as positive, the ED experience was dominated by negative experiences relating to very basic issues such as a lack of help with eating, drinking, toileting and discomfort from long waits on hard trolleys. Participants reported that communication and involvement in decision making could be improved, including involving next of kin, who were viewed as critical to supporting vulnerable older people during sometimes very protracted waits. Conclusion: Frailty reflects a vulnerability and a need for support in basic activities of daily living, which EDs in this study, and perhaps more widely, are not set up to provide. Changes at the levels of clinical practice and service design are required to deliver even the most basic care for older people with frailty in the ED environment.